Multicenter Evaluation of Noise Levels and Staff Perceptions Across Laser Technologies During Holmium Laser Enucleation of the Prostate: A Prostate Enucleation Collaborative Initiative - Jessica Wu; Amanda E. Kahn; Benjamin Dalkin; Satvik Kuravi; Adam Cohen; Charles Klose; Eric Qualkenbush; Bryce Baird; Karen L. Stern; Smita De; Dane Klett; Rajat Jain; et al. (Lasers in Surgery and Medicine, 2026)
ABSTRACT Introduction Operating room (OR) noise during holmium laser enucleation of the prostate (HoLEP), particularly from laser activation, may impair surgical workflow and staff performance. Methods 84 HoLEP procedures were recorded at three academic institutions between June 2024 and January 2026. Laser platforms included Lumenis Moses 2.0, Quanta Litho 150, Quanta Magneto, and Dornier Thulio. Sound measurements were obtained using a standardized smartphone‐based system during three phases: laser‐off (baseline), idle (not firing), and active lasing. Acoustic metrics included average sound level (LAeq), peak sound level (Lcpeak), and sound levels exceeded for 10%, 50%, and 90% of the recording time (L10, L50, and L90). Background noise correction was performed using baseline measurements to account for ambient noise and isolate laser‐related sound. OR staff completed a validated survey assessing perceived noise burden (0–10 scale). Results Background‐corrected noise during active lasing differed significantly by platform. Litho demonstrated lower mean noise levels compared to Thulio for LAeq (60.6 vs. 68.2 dB, p = 0.023) and L10 (61.5 vs. 70.6 dB, p = 0.023), while Moses had higher LAeq compared to Litho (63.1 vs. 60.6 dB, p = 0.043). Overall, Litho had the lowest noise levels, whereas Thulio had the highest. Survey responses paralleled these findings. Litho was associated with lower perceived overall effort (2.1 ± 0.9), while Moses demonstrated higher overall effort (3.6 ± 1.2) for communication and concentration (Figure 2). Significant pairwise differences were observed between Moses and Litho (all p < 0.05). Trends were consistent across sites. Conclusions Noise levels during HoLEP varied by laser technology and correlated with differences in perceived communication and cognitive effort. Litho demonstrated the lowest acoustic burden, while Moses and Thulio had higher noise exposure. These findings highlight the impact of laser selection on the OR environment and intraoperative team performance.